2019
DOI: 10.1038/s41598-019-53571-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the thorium-immobility paradigm

Abstract: Thorium is the most abundant actinide in the Earth’s crust and has universally been considered one of the most immobile elements in natural aqueous systems. This view, however, is based almost exclusively on solubility data obtained at low temperature and their theoretical extrapolation to elevated temperature. The occurrence of hydrothermal deposits with high concentrations of Th challenges the Th immobility paradigm and strongly suggests that Th may be mobilized by some aqueous fluids. Here, we demonstrate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Significant HREE and Th depletion in the altered samples relative to LREE likely reflects higher mobility of Th relative to LREE, and therefore Th was precipitated earlier (relative to LREE), together with the HREE, in the alteration domains. As an alternative hypothesis, contrary to the widely held view that Th is an immobile element, Nisbet et al (2019) experimentally demonstrate that in high temperature sulfate-bearing aqueous fluids (i.e., between 175 and 250 • C), ThO 2 is extremely soluble, and therefore that Th is highly mobile. Experimental work has also shown that LREE complexes in fluids generally show more stability than HREE complexes at temperatures higher than 150 • C, especially F-bearing fluids (Williams-Jones et al, 2012).…”
Section: Inferences From Incompatible Elements and Reementioning
confidence: 67%
“…Significant HREE and Th depletion in the altered samples relative to LREE likely reflects higher mobility of Th relative to LREE, and therefore Th was precipitated earlier (relative to LREE), together with the HREE, in the alteration domains. As an alternative hypothesis, contrary to the widely held view that Th is an immobile element, Nisbet et al (2019) experimentally demonstrate that in high temperature sulfate-bearing aqueous fluids (i.e., between 175 and 250 • C), ThO 2 is extremely soluble, and therefore that Th is highly mobile. Experimental work has also shown that LREE complexes in fluids generally show more stability than HREE complexes at temperatures higher than 150 • C, especially F-bearing fluids (Williams-Jones et al, 2012).…”
Section: Inferences From Incompatible Elements and Reementioning
confidence: 67%
“…The published data on this speciation are restricted almost entirely to temperatures below 100°C, with most of the data being for ambient conditions (Rand et al, 2008). We recently launched a research program to address this knowledge gap by conducting solubility experiments involving crystalline ThO 2 at temperatures >175°C in chloride-and sulfate-bearing systems, i.e., systems containing ligands expected to be important in natural hydrothermal systems (Nisbet et al, 2018(Nisbet et al, , 2019. These experiments indicated that SO 4 2has a major impact on the solubility and mobility of Th at elevated temperature (175-250°C), even if the concentrations of SO 4 2-(>0.5m) are modest (Nisbet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We recently launched a research program to address this knowledge gap by conducting solubility experiments involving crystalline ThO 2 at temperatures >175°C in chloride-and sulfate-bearing systems, i.e., systems containing ligands expected to be important in natural hydrothermal systems (Nisbet et al, 2018(Nisbet et al, , 2019. These experiments indicated that SO 4 2has a major impact on the solubility and mobility of Th at elevated temperature (175-250°C), even if the concentrations of SO 4 2-(>0.5m) are modest (Nisbet et al, 2019). A notable gap in our current knowledge is a lack of understanding of the behavior of Th in carbonate-bearing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear energy has become one of the most important alternative energy sources especially after the mid-20th century (Rezaei et al, 2017). As is known, the most important raw materials of this energy are uranium and thorium (Li et al, 2019;Nisbet et al, 2019). In conjunction with this, nuclear accidents (Bailiffa et al, 2016) (exposure to radioactive dose due to radioactive contamination by presence of radioactive materials affecting people and/ or the environment, or an event involving radioactive contamination) (Ahearne, 2011;Goodfellow et al, 2011), testing of nuclear weapons (Pravalie, 2014), the spread of radioactive substances to the environment because of waste from nuclear industry cause excessive exposure of all living organisms to radiation in the environment (Kobashi et al, 2020;Sevbitov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%